PENGARUH RETURN ON ASSET, RETURN ON EQUITY, NET PROFIT MARGIN DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM (Studi Empiris Perusahaan Sub Sektor Aluminium dan Pertambangan Emas yang terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Hendri Jun; Gita Suliska; Sri Wineh (Universitas Muara Bungo, 2022)
The business world is currently experiencing very rapid development, investors must at any time conduct an analysis of a company, using the company's financial statements to determine the condition of the company. In investing, an investor must expect a profit (Return). The purpose of this study was to analyze the factors that affect stock returns in the Aluminum and Mining Industry Sub-Sector Companies listed on the Indonesian Stock Exchange. This type of research is quantitative research using secondary data, with looking at company data obtained through the annual report obtained from www.idx.co.id. The method used to determine the sample is purposive sampling method using multiple regression analysis with the support of SPSS (Statistical Product and Service Solution) 23. The results of this study indicate that partially Debt to Equity Ratio and Return On Equity have an effect on Stock Return. While the Return On Assets and Net Profit Margin have no effect on Stock Return. Simultaneously Debt to Equity Ratio, Return On Assets, Return On Equity and Net Profit Margin affect Stock Return